2018
DOI: 10.1002/cam4.1489
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of combined pretreatment lymphocyte counts and body mass index in patients with head and neck cancer treated with radiation therapy

Abstract: We aimed to investigate the prognostic significance of combined pretreatment lymphocyte counts (LCs) and body mass index (BMI) in patients with head and neck cancer (HNC) treated with radiation therapy (RT). Nine hundred and twelve patients with HNC who were treated with RT were retrospectively reviewed. Survival was analyzed by stratifying the patients according to pretreatment LCs and BMI. Patients with low pretreatment LCs and BMI were characterized by a more advanced T stage, fewer nasopharyngeal subsites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…However, tumours may suppress lymphocyte activation and recruitment by inhibiting dendritic cell differentiation and activation, tumour‐associated macrophages, and the subsequent infiltration of the regulatory T cells (Mantovani et al., 2008). Wu et al investigated 912 patients with HNC and reported that patients with low pretreatment lymphocyte counts had significantly poorer OS and distant metastasis‐free survival than did those with high pretreatment lymphocyte counts (Wu et al., 2018). Taken together, a low PNI value may reflect lymphocytopaenia and/or hypoalbuminaemia, and both are indicators of poor prognosis in patients with OSCC (Milne et al., 2012; Schueneman et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, tumours may suppress lymphocyte activation and recruitment by inhibiting dendritic cell differentiation and activation, tumour‐associated macrophages, and the subsequent infiltration of the regulatory T cells (Mantovani et al., 2008). Wu et al investigated 912 patients with HNC and reported that patients with low pretreatment lymphocyte counts had significantly poorer OS and distant metastasis‐free survival than did those with high pretreatment lymphocyte counts (Wu et al., 2018). Taken together, a low PNI value may reflect lymphocytopaenia and/or hypoalbuminaemia, and both are indicators of poor prognosis in patients with OSCC (Milne et al., 2012; Schueneman et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…High CBR associated with poor survival could be also understood from the perspective of inflammation. Previous studies indicated that CEA in patients with CRC could induce the secretion of IL-6, and that the levels of CEA and IL-6 were positively correlated (16,53). It was noted that IL-6 could induce fat loss in cancer cachexia via different approaches, such as promoting white adipose tissue lipolysis (54) and decreasing muscle mass (55), which could result in a decreased BMI in these patients (56).…”
Section: Discussionmentioning
confidence: 99%
“…For BMI, its application in prognosis was largely blocked by inconsistent criteria and conflicting results, as aforementioned ( 10 – 14 ). Similarly, some reports indicated that combining BMI with other markers, such as lymphocyte counts, could improve the prognostic efficacy for patients with head and neck cancer who underwent radiation therapy ( 16 ). Recently, Xie et al ( 42 ) conducted a study that included 2,471 patients with CRC and found that the neutrophil-BMI ratio was a useful prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor infiltrating lymphocytes (TILs) in NPC were common significantly associated with better survival, which was supposed to be an independent and potential prognostic biomarker (52). And several data have also showed that higher peripheral blood lymphocytes predicted a favorable outcome in NPC and other head and neck caner (18,45,53,54).…”
Section: Discussionmentioning
confidence: 99%